Biological, genetic, neurological and environmental influences on homosexuality—a narrative review - Alagha, Michel; Antoun, Freddy; Bacha, Christine; El Nabbout, Tiara; El Khoury, Noura B. (Frontiers in Behavioral Neuroscience, 2025)
Homosexuality is an intricate and multifactorial phenomenon affected by the interaction of biological, genetic, neurological and environmental factors. This paper examines the interplay of homosexuality determinants. Biological determinants such as the role of androgen levels, the fraternal birth order effect and maternal immune response contribute to shaping sexual orientation. Additionally, genetic influences are also assessed. These include the potential role of X chromosome, the possible link of fragile X mental retardation neighbor gene (FMR1) to sexual orientation, the function of genetic variants such as COMT an MTHFR, as well as connection with chromosomes 7, 8, 13 and 14. Furthermore, neurologic factors such as the role of the hypothalamus are assessed to highlight their contribution to sexual preference and attraction mediation. Lastly, childhood gender nonconformity and early exposure to traumatic events are among the environmental influences that contribute to the development of homosexuality. By incorporating various perspectives, this paper seeks to present a thorough overview of the multiple factors influencing sexual orientation, while emphasizing the importance of ongoing interdisciplinary research in this area.